Progressive Impairment of Mismatch Negativity Is Reflective of Underlying Pathophysiological Changes in Patients With First-Episode Psychosis - Lho, Silvia Kyungjin; Kim, Minah; Park, Jihye; Hwang, Wu Jeong; Moon, Sun-Young; Oh, Sanghoon; Kwon, Jun Soo (Frontiers in Psychiatry, 2020)
Background: Although mismatch negativity (MMN) is associated with the pathophysiology of schizophrenia, whether MMN progressively worsens during the initial years of psychotic disorder has not yet been sufficiently studied. We aimed to investigate whether longitudinal reduction of MMN occurs in patients with first-episode psychosis (FEP) and whether it is reflective of change in cognitive functioning or clinical status. Methods: MMN and the clinical status of 25 patients with FEP were measured and the Trail Making Test (TMT) was administered at baseline and reassessed after 1 year of usual treatment. The MMN of 25 matched healthy controls (HCs) was measured at baseline. Repeated-measures analysis of variance was used to compare MMNs at baseline among the groups, and paired t-test was utilized to compare the baseline and 1-year MMN amplitudes of FEP patients. To identify the association between changes in MMN and changes in cognitive, symptomatic, or functional status over 1 year, multiple regression analysis was used to control for other possible confounders. Results: MMN amplitudes at baseline were significantly attenuated in FEP patients compared to those in HC. The one-year follow-up MMN amplitude decreased significantly at the Fz electrode site in the FEP group. Additionally, the decreased MMN amplitude significantly correlated with worsened TMT part B (TMT-B) performance over 1 year but did not correlate with symptomatic or functional improvement. Conclusions: FEP patients with an MMN amplitude reduction showed worsening of cognitive functioning, which might reflect pathophysiological progression during the early years of a psychotic episode.